Application of Virtual Reality Via the Delightex Platform for Enhancing Proficiency in Arabic Speaking Skills - Humayrah, Alifka Humayrah; Ismail, Moh.; Thalia, Mannar (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Proficiency in speaking skills (maharah kalām) is crucial for Arabic language acquisition, yet conventional, teacher-centered approaches often provide limited opportunities for contextual communication. This study develops and evaluates an immersive Virtual Reality (VR) learning medium using the Delightex platform to enhance students’ Arabic speaking performance. Employing an R&D design with the ADDIE model, participants were 30 seventh-grade female students at a modern Islamic boarding school. Data were collected via observations and semi-structured interviews, speaking tests (pre–post), and questionnaires, and analyzed using mixed methods. Results indicate substantial improvement: the average score increased from 66.1 (pre-test) to 85.5 (post-test), with 28 of 30 students (98%) meeting the minimum mastery criterion KKM. The normalized gain (N-Gain) attained a value of 0.57, classified as medium-high. Qualitative findings show higher engagement, reduced speaking anxiety, better contextual vocabulary use, and increased confidence during avatar-based dialogues in a virtual library scenario. The findings indicated that Delightex-VR media is highly efficient in enhancing maharah kalām and aids in the advancement of technology-driven Arabic language learning methods in Islamic boarding schools.